Effect of Fe2O3 as Catalyst on Biogas Production from Dry Banana Leaves - P Jena, Shakti; K Nirala, Malendra; K Acharya, Saroj (International Journal of Engineering and Technology, 2018)
Anaerobic digestion (AD) of dry banana leaves to produce biogas and the biogas production patterns under the influence of additives has been studied in present work. The impact of different dosage of Fe2O3 catalyst along with urea added by 2% based on dry weight of banana leaves added in sewage water inoculums for production of biogas were observed for 50 days of retention time. Simultaneous scrubbing arrangement was arranged to purify the raw biogas to enrich the methane content in the upgraded biogas. The results revealed that sewage water (S) with urea reached the peak CH4 concentration in biogas (64.72%) during 38 days, as compared to S+Urea+15 mg Fe2O3 (67.25%) in 30 days and S+Urea+25 mg Fe2O3 (65.15%) in 34 days. Addition of Fe2O3 indicated a reduction of lag phase in CH4 generation and attains the peak CH4 concentration at a faster rate. Purification of the raw biogas with 1 N NaOH solution has shown a drastic enrichment in CH4 content by absorption of CO2. The peak CH4 content after purification was found to be 83.24, 86.02 and 84.25% for S+Urea, S+Urea+15 mg Fe2O3 and S+Urea+25 mg Fe2O3 inoculums respectively.Â Â